Montana dawn - Wallace, Stone, 1957- (Avalon Books, 2010)
When the remnants of a ruthless outlaw gang invade the peaceful desert setting Montana Dawn shares with her gentleman husband, little does the girl suspect that her long-dormant spirit for a life far removed from her domestic existence will be passionately re-ignited and that circumstances will soon brand her as the most wanted female criminal in the Southwest. With a bounty on their head and a determined posse hot in pursuit, Montana Dawn and her outlaw companion Walt Egan share romance and danger across the unrelenting Nevada terrain as they attempt to stay ahead of the law and escape into Mexico to start a new life. Their destination is close at hand. But will they survive to realize their ambition?